Atomically Thin Nanosheets Confined in 2D Heterostructures: Metal‐Ion Batteries Prospective. Issue 20 (23rd April 2021) - Khan, Abbas; Azadmanjiri, Jalal; Wu, Bing; Liping, Liao; Sofer, Zdeněk; Min, Jiakang
Abstract: Owing to the surge of energy storage devices, lithium and beyond‐lithium metal ion batteries (MIBs) have gained considerable research attention. The large size and multivalent ions drastically deteriorate the performance of conventional battery electrode materials which demands unique types of structures in order to fulfill the electrode requirements of next‐generation MIBs. Developing atomically thin nanosheets confined in 2D heterostructures is a favorable choice to synergistically handle the deficiencies of individual 2D materials and achieve distinct physical and electrochemical properties, retaining their 2D features. This article sheds light on the significance and characteristics of graphene‐based and beyond‐graphene 2D heterostructures as electrode materials in lithium‐ion, sodium‐ion, potassium‐ion, magnesium‐ion, and aluminum‐ion batteries. In this regard, the pathways for the selection of 2D heterostructures electrode materials and their possible geometric configurations are first recognized. Second, the fundamental science, underlying charge storage mechanisms, and robust interfacial charge transfer processes in 2D heterostructures are discussed comprehensively in the context of recent computational studies. Third, the recent state‐of‐the‐art experimental approaches for the fabrication of novel 2D heterostructures and their performance as anode and cathode materials for MIBs are discussed systematically. Finally, the current challenges facing 2D heterostructures and potential future research directions in the context of advanced MIBs are highlighted. Abstract : Arrangement of 2D materials (2DMs) in a heterostructure configuration is an effective strategy for achieving a synergistic combination of their individual characteristics and overcoming their respective deficiencies. This article aims to highlight the current challenges faced by 2DMs namely graphene, transition metal dichalcogenides, oxides, carbides and nitrides, and the importance of their heterostructures for next generation alkali metal ion batteries.